The spectrum of computerized tomography (CT) findings in central nervous system (CNS) infection due to Cryptococcus neoformans var. gattii in immunocompetent children - CORRÊA Maria do Perpétuo Socorro Costa; SEVERO Luiz Carlos; OLIVEIRA Flávio de Mattos; IRION Klaus; LONDERO Alberto Thomaz (Universidade de São Paulo (USP), 2002)
Cranial CT scans of eleven immunocompetent children with central nervous system (CNS) infection due to Cryptococcus neoformans var. gattii were retrospectively reviewed. These children had an average age of 8.8 years and positive culture for C. n. var. gattii in cerebrospinal fluid. The most common signs and symptoms were headache, fever, nuchal rigidity, nausea and vomiting. No normal cranial CT was detected in any patient. Hypodense nodules were observed in all patients . The remaining scan abnormalities were as follows: nine had diffuse atrophy, six had hydrocephalus, and five had hydrocephalus coexistent with diffuse atrophy.